Examining the Impact of Knowledge of Mathematics on Academic Achievement in Physics, Among Students at Mawuli Senior High School, Ghana - Yuoni, Anthony Babategrimine; Amadu, Uthman; Jakalia, Issahaku Sontaa (Journal of Education and Practice, 2024)
Purpose: The aim of this action research is to evaluate the impact of mathematical knowledge on students' academic performance in physics at Mawuli School, Ho. Methodology: A teacher-made test was the instrument used for data collection in this study. The test consisted of questions in both mathematics and physics. The mathematics questions were strategically selected to align with concepts relevant to the physics curriculum. Pre-test and post-test were administered using similar sets of questions. Data analysis employed descriptive statistics, paired t-tests, correlation analysis, and regression analysis. Findings: The study findings indicated a statistically significant positive correlation between students' mathematical knowledge and their performance in physics. Also, there was no significant difference in the performance of males and females students. Unique Contribution to Theory, Practice and Policy: It was therefore recommended that physics teachers prioritize assessing and enhancing students' mathematical proficiency prior to introducing physics topics that require mathematical application.